Eksplorasi berpikir kreatif siswa dalam pemecahan masalah matematika berbasis computational thinking - Tina Rosyana; Dwi Juniati; Siti Khabibah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Creativity in problem-solving needs to be strengthened through a systematic thinking framework. This study aims to explore students' creative thinking patterns in solving mathematics problems based on computational thinking (CT). A descriptive qualitative approach was employed, involving three junior high school students in West Bandung Regency representing high, medium, and low levels of mathematical ability. Data were collected through semi-structured in-depth interviews and essay test focusing on four elements of CT (decomposition, pattern recognition, abstraction, and algorithmic thinking) and four indicators of creative thinking (fluency, flexibility, originality, and elaboration). The results revealed High-ability students demonstrated strong integration between CT and conceptual creativity. Medium-ability students exhibited strategic flexibility, although their symbolic representations were not yet stable. In contrast, low-ability students tended to rely on procedural approaches. This study confirms that CT can function as a systematic thinking framework to foster creativity in 21st-century mathematics learning. It also contributes theoretically to understanding the dynamic relationship between CT and mathematical creative thinking and practically to the design of pattern-based tasks that stimulate student creativity.